2019
DOI: 10.1007/s12046-019-1082-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for text summarization using optimal combination of sentence scoring methods

Abstract: In this paper, a novel multi-document summarization scheme based on metaheuristic optimization is introduced that generates a summary by extracting salient and relevant sentences from a collection of documents. The proposed work generates optimal combinations of sentence scoring methods and their respective optimal weights to extract the sentences with the help of a metaheuristic approach known as teaching-learning-based optimization. In addition, the proposed scheme is compared to two summarization methods th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…A sentence may contain various features of the text on the basis of which a score can be assigned to the sentence. In the proposed approach, eight text features (Verma & Om, 2019a) have been considered as follows: Significant words: Significance of a word conveys its contribution of important information in a sentence. A sentence with significant words is also considered significant.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A sentence may contain various features of the text on the basis of which a score can be assigned to the sentence. In the proposed approach, eight text features (Verma & Om, 2019a) have been considered as follows: Significant words: Significance of a word conveys its contribution of important information in a sentence. A sentence with significant words is also considered significant.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Ferreira et al (Ferreira et al, 2013) worked on this problem and found the best combinations of sentence scoring techniques using quantitative and qualitative assessments. Similarly, Verma and Om (Verma & Om, 2019a) also proposed a metaheuristic-based approach to find several good combinations of the sentence scoring techniques and test these combinations on DUC datasets.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…MirShojaee et al [18] propose a biogeography-based metaheuristic optimization method (BBO) for extractive text summarization. In [19], authors try to generate optimal combinations of sentence scoring methods and their respective optimal weights for extracting the sentences with the help of a metaheuristic approach known as teachinglearning-based optimization.…”
Section: Related Workmentioning
confidence: 99%
“…They compute the importance of a sentence in extractive single and multi-document summarizations. The work of Verma and Om (2019) extracts the summary sentences with the help of a meta heuristic approach known as teaching-earning-based optimization. The work of Sariki et al (2019) contains three different concurrent pipelines to improve the effectiveness of the summarization process.…”
Section: Introductionmentioning
confidence: 99%